Permeability Of Interlanguage System: A Case Study OfStudents Learning English As A Foreign LanguageIn SMP Muhammadiyah 5 Surakarta - Maryana ., Lestari Kelik; , Prof. Dr. Endang Fauziati, M. Hum.; , Drs. Djoko Srijono, M. Hum (2013)
The research deals with permeability of students' interlanguage system that reflects in students' composition of SMP Muhammadiyah 5 Surakarta. The aims of the research are (1) to describe how the mother tongue system influences in the students' interlanguage system, (2) to describe how the target language system influences in the students' interlanguage system, (3) to describe to what extend the students' mother tongue influence the students' interlanguage system, (4) to describe to what extend the students' target language influences the students' interlanguage system, and (5) to describe the degree of the influences from both the mother tongue and target language in the students' interlanguage system. The type of this research is qualitative research. The data of this research are erroneous sentences found in the students' compositions. The method of collecting data is elicitation and document analysis. The writer uses descriptive analysis by Celce Marcia and a modified framework of Error Analysis by Shridar (2009:136) as a technique for analyzing data. The steps are: (1) identifying error, (2) classifying error, (3) identifying source of error, (4) describing the degree of influeces, (5) drawing conclusions. The results are (1) the influence of mother tongue (Indonesian) in the students' IL is in the term of (a) morphological level including Indonesian abbreviation, Indonesian word, and the use of Indonesian word with slight modification, and (b) syntactic level including the use of Indonesian pattern in phrase and the use of Indonesian pattern in sentence, (2) the influence of target language (English) in the students' IL is in the term of (a) morphological level including free morpheme involves false friend, omission of article, addition of article, and misformation, and bound morpeme involves omission of -s in plural form, and (b) syntactic level including the use V1 instead of V2, omission of be as copula, and preposition-omission of preposition, addition of preposition and misuseof preposition, (3) the influence frequency of the mother tongue to students' IL system is as 48%, (4) the target language to the students' IL system as 52%, and (5) the influence of students' target language (52%) to their IL system is greater than the influence of students' mother tongue (48%). The research result shows that learners' interlanguage open to to influence from the outside and influence from the inside. It is progressively approaches target language as a result of learners' attempt on constructing a new linguistic system.